Towards a contemporary social care 'prevention narrative' of principled complexity: An integrative literature review. (15th May 2021) - Verity, Fiona; Richards, Jonathan; Read, Simon; Wallace, Sarah
Abstract: Prevention has become increasingly central in social care policy and commissioning strategies within the United Kingdom (UK). Commonly there is reliance on understandings borrowed from the sphere of public health, leaning on a prevention discourse characterised by the 'upstream and downstream' metaphor. Whilst framing both structural factors and responses to individual circumstances, the public health approach nonetheless suggests linearity in a cause and effect relationship. Social care and illness follow many trajectories and this conceptualisation of prevention may limit its effectiveness and scope in social care. Undertaken as part of a commissioned evaluation of the Social Services and Wellbeing Act (2014) Wales, a systematic integrative review was conducted to establish the key current debates within prevention work, and how prevention is conceptually framed, implemented and evaluated within the social care context. The databases Scopus, ASSIA, CINAHL and Social Care Online were initially searched in September 2019 resulting in 52 documents being incorporated for analysis. A further re‐run of searches was run in March 2021, identifying a further 14 documents, thereby creating a total of 66. Predominantly, these were journal articles or research reports ( n  = 53), with the remainder guidance or strategy documents, briefings or process evaluations ( n  = 13). These were categorised by their primary theme and focus, as well as document format and research method before undergoing thematic analysis. This highlighted the continued prominence of three‐tiered, linear public health narratives in the framing of prevention for social care, with prevention work often categorised and enacted with inconsistency. Common drivers for prevention activity continue to be cost reduction and reduced dependence on the care system in the future. Through exploring prevention for older people and caregivers, we argue for an approach to prevention aligning with the complexities of the social world surrounding it. Building on developments in complexity theory in social science and healthcare, we offer an alternative view of social care prevention guided by principles rooted in the everyday realities of communities, service users and caregivers.